2018
DOI: 10.1038/s41598-018-32479-y
|View full text |Cite
|
Sign up to set email alerts
|

Effective surface conductivity of optical hyperbolic metasurfaces: from far-field characterization to surface wave analysis

Abstract: Metasurfaces offer great potential to control near- and far-fields through engineering optical properties of elementary cells or meta-atoms. Such perspective opens a route to efficient manipulation of the optical signals both at nanoscale and in photonics applications. In this paper we show that a local surface conductivity tensor well describes optical properties of a resonant plasmonic hyperbolic metasurface both in the far-field and in the near-field regimes, where spatial dispersion usually plays a crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 75 publications
(136 reference statements)
0
17
0
Order By: Relevance
“…The details and limitations of the discrete dipole model implementation are described in Refs. [13,20]. We verify theoretical results with the full-wave numerical simulation in COMSOL Multiphysics.…”
Section: Model and Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…The details and limitations of the discrete dipole model implementation are described in Refs. [13,20]. We verify theoretical results with the full-wave numerical simulation in COMSOL Multiphysics.…”
Section: Model and Methodsmentioning
confidence: 72%
“…On the one hand, we perform the extraction of effective conductivity tensor from the reflection spectra by applying the zero-thickness approximation developed in Refs. [13,14]. The reflection spectra can be simulated in CST Microwave Studio or measured experimentally.…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we only consider TM modes confined to metasurfaces. The dispersion relation of TM modes in metasurfaces is given as [58,59] (4)…”
Section: D Planar Hyperbolic Materialsmentioning
confidence: 99%
“…. Similar to the electrically biased patterned elements with arbitrary shapes, the parameter retrieval method can be used under the applied magnetic bias [55]. Given the discussion of the above three sections, it is observed that assuming the surface conductivity of graphene as:…”
Section: Graphene Sheet Under Magnetic Biasmentioning
confidence: 99%